1985
DOI: 10.1017/s0043174500082540
|View full text |Cite
|
Sign up to set email alerts
|

Method for Bioassaying Chlorsulfuron in Soil and Water

Abstract: Bioassay techniques were evaluated for the determination of chlorsulfuron {2-chloro-N-[[(4-methoxy-6-methyl-1,3,5-triazin-2-yl)amino] carbonyl] benzenesulfonamide} residues in soil and water. A linear response of corn (Zea maysL.) primary root length to chlorsulfuron concentrations (InX+1) of 0.0 to 16.0 μg/L was observed in the water bioassay. Several soil extraction bioassay methods were attempted and found to be highly variable. A Ca(OH)2soil extraction bioassay technique produced a linear response of prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Hsiao and Smith (6), Groves and Foster (5), Mersie and Foy (10), and Morishita et al (11) reported that it is possible to use root bioassays for the detection of chlorsulfuron.…”
Section: Weed Technologymentioning
confidence: 99%
“…Hsiao and Smith (6), Groves and Foster (5), Mersie and Foy (10), and Morishita et al (11) reported that it is possible to use root bioassays for the detection of chlorsulfuron.…”
Section: Weed Technologymentioning
confidence: 99%
“…Bioassay procedures for determining chlorsulfuron in water and soil at 0.1 ppb level have been reported by Morishita et al (1985), Hsiao and Smith (1983), and Du Pont (1980). Kelley et al (1985) have presented an enzyme immunoassay procedure for determining chlorsulfuron in soil extracts at 0.4-1.2 ppb levels.…”
mentioning
confidence: 99%
“…Various plant species have been used in bioassays for the determination of ALS-herbicides in soil, primarily using root measurements because of the inhibiting effect of ALS-herbicides on cell division at the root tips of susceptible plants. Some of the crops that have been used are corn for chlorsulfuron (Anderson & Humburg, 1987;Groves & Foster, 1985;Hsiao & Smith, 1983;Morishita et al, 1985), sunflower for MON-37500 and triasulfuron (Hernández-Sevillano et al, 2001), lentil for metsulfuron (Szmigielska et. al., 1998), and canola for imazethapyr (Szmigielska & Schoenau, 1999).…”
Section: Plant Bioassay Techniquesmentioning
confidence: 99%